Marine And Coastal Heavy Mineral Placers: The Role Of Radiometric Techniques In Exploration, Assessment And Process Control - David G. Jones (International Marine Minerals Society, 1995)
Radiometric surveys of the beach and nearshore zone of the Dutch Frisian Islands have identified sands enriched in heavy minerals. The areas of heavy mineral concentration have been mapped in detail using a state of the art towed gamma-ray detector, which gives improved sensitivity through the use of new detector materials and improved data processing techniques. The detector provides continuous measurement of sea floor radioactivity (and of a number of other parameters) and can be used simultaneously with other survey techniques, such as echo sounding, sidescan sonar and shallow seismic profiling. It enables a rapid, and cost effective, assessment of the surface distribution of heavy minerals to be made. The heavy mineral suite includes magnetite, ilmenite, garnet, rutile and zircon. These minerals contain 1-3 orders of magnitude more U and Th, in terms of their activity concentrations, than the accompanying light minerals (mainly quartz). Since the heavy mineral composition of the sands appears to be relatively constant along the Dutch Frisian Island chain, the U and Th concentrations can be used to provide a quick estimate of the heavy mineral content. The sea floor radiometric measurements allow sediment sampling for more detailed analysis to be highly targetted. The zones of heavy mineral enrichment are generally sub-parallel to the coast and are usually confined to water depths of 5-10 m. There is a close correlation with sand bars on the shoreface, the highest radioactivity typically occurring just seaward of the crest of these features. As well as being used for heavy mineral exploration, similar radiometric methods can be applied to mineral processing. Gamma-ray detection systems can be used to provide rapid analysis in the process stream enabling on-line grade control and optimisation of processing, from excavation of mineral sands to the final products.